2021
DOI: 10.3389/fmicb.2021.761067
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota Interplay With COVID-19 Reveals Links to Host Lipid Metabolism Among Middle Eastern Populations

Abstract: The interplay between the compositional changes in the gastrointestinal microbiome, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) susceptibility and severity, and host functions is complex and yet to be fully understood. This study performed 16S rRNA gene-based microbial profiling of 143 subjects. We observed structural and compositional alterations in the gut microbiota of the SARS-CoV-2-infected group in comparison to non-infected controls. The gut microbiota composition of the SARS-CoV-2-infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…In general, the main alternations in the gut microbiome of COVID-19 infected individuals were the higher abundance of; Bacteroides, Streptococcus, Fusobacterium, Campylobacter, Lactobacillus, Proteobacteria, Enterococcaceae, Enterococcus, Rothia, Pseudomonas, Veillonella, Clostridium, and Staphylococcaceae, and lower presence of; Coprococcus, Faecalibacterium, Eubacterium, Roseburia, Bi dobacterium, and Blautia. In our review, ve studies reported an increase in Bacteroides in COVID-19 patients [51,61,[78][79][80] while only one reported a decrease in them [42]. These studies observed a rise in Bacteroides stercoris, Bacteroides dorei, Bacteroides vulgatus, Bacteroides massiliensis, Bacteroides oleiciplenus, and Bacteroides ovatus as main species in fecal samples of COVID-19 patients.…”
Section: Dysbiosismentioning
confidence: 94%
See 3 more Smart Citations
“…In general, the main alternations in the gut microbiome of COVID-19 infected individuals were the higher abundance of; Bacteroides, Streptococcus, Fusobacterium, Campylobacter, Lactobacillus, Proteobacteria, Enterococcaceae, Enterococcus, Rothia, Pseudomonas, Veillonella, Clostridium, and Staphylococcaceae, and lower presence of; Coprococcus, Faecalibacterium, Eubacterium, Roseburia, Bi dobacterium, and Blautia. In our review, ve studies reported an increase in Bacteroides in COVID-19 patients [51,61,[78][79][80] while only one reported a decrease in them [42]. These studies observed a rise in Bacteroides stercoris, Bacteroides dorei, Bacteroides vulgatus, Bacteroides massiliensis, Bacteroides oleiciplenus, and Bacteroides ovatus as main species in fecal samples of COVID-19 patients.…”
Section: Dysbiosismentioning
confidence: 94%
“…was another common genus mentioned by four articles in our review. One study reported a decrease in the levels of this bacterium [75], while another study reported increasing patterns of this bacteria [42]; in addition, its presence in the gut microbiome of CRC patients has been linked to more severe disease [44] and increased levels of this bacterium have been reported after COVID-19 recovery [46]. In a similar study investigating the alterations of gut microbial composition among COVID-19 patients, the authors reported declining bene cial species and increasing opportunistic pathogens such asBlautia sp.…”
Section: Dysbiosismentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, SARS-CoV-2 uses the S protein to bind ACE2, yet attaches to the host cell with a higher affinity compared to SARS-CoV [44][45][46][47]. ACE2 is expressed on a variety of cells in the lungs and the gut, including epithelial cells of the airways and alveoli, vascular endothelial cells, and macrophages [48][49][50][51]. The transmembrane serine protease 2 (TMPRSS2) is also needed for SARS-CoV-2 entry [52].…”
Section: The Innate and Adaptive Immune Responses Associated With Sar...mentioning
confidence: 99%